Development Of An Ergonomic Banana Chopping Machine With Consideration of The Anthropometry of Indonesian People - Pical, Ariel Julianus; Fortunatus, Yoel; Damayanti, Florencia Agatha; Narendra, Ravael Dimas Eka; Tentua, Johan Patrick; Irawati, Desrina Yusi (Fakultas Sains dan Teknologi Universitas Islam Negeri Sultan Syarif Kasim Riau, 2023)
Micro-and medium-sized enterprises are the axis of the economy, especially in Indonesia, and have an essential role in supporting the running of the national economy. With the rapid development of technology. Innovation is the primary key to improving a business so that it can compete even on an international scale. This study aims to design a banana chip chopper machine that considers ergonomic values, considering that there are still many banana chip chopper machines sold on the market without considering ergonomic values in the product. They are like the height of the machine, which is different from the average height of the Indonesian people. The chopping process is still manual, and it is challenging to create consistent quality pieces of chips because the slicing is still manual and must adjust to the size of the machine. It does not match the average height of Indonesians, where which can result in injury to the hands and muscles of the hands. Then the study results will show an ergonomic banana-chopping machine with a height and size that match the anthropometric data of Indonesian people